The Evolving Role of Maintenance Therapy Using Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors (EGFR TKIs) in the Management of Advanced Non-Small-Cell Lung Cancer - Huang, Chao H.; Powers, Benjamin C. (Clinical Medicine Insights. Oncology, 2012)
The epidermal growth factor receptor (EGFR) plays an important role in the development of many cancers, including non-small cell lung cancer. Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKIs) are a class of novel biologically-targeted agents widely used in the management of recurrent non-small cell lung cancer. Erlotinib, one of the EGFR TKIs, is currently FDA approved in second and third line therapy. However, recent studies showed that erlotinib is also effective as maintenance therapy after initial chemotherapy, improving disease free survival and possibly overall survival. Our current understanding of erlotinib's mechanism of action, with the discovery that EGFR mutation confers higher response rate, has propelled this agent into the first line setting. Advances in molecular testing and clinical research of this agent and other agents in this class will eventually change the way we utilize EGFR TKIs in the near future.